Adipocytes and Stromal Cells Regulate Brown Adipogenesis Through Secretory Factors During the Postnatal White-to-Brown Conversion of Adipose Tissue in Syrian Hamsters - Mae, Junnosuke; Nagaya, Kazuki; Okamatsu-Ogura, Yuko; Tsubota, Ayumi; Matsuoka, Shinya; Nio-Kobayashi, Junko; Kimura, Kazuhiro (Frontiers in Cell and Developmental Biology, 2021)
Brown adipose tissue (BAT) is a specialized tissue that regulates nonshivering thermogenesis. In Syrian hamsters, interscapular adipose tissue is composed primarily of white adipocytes at birth, which is converted to BAT through the proliferation and differentiation of brown adipocyte progenitors and the simultaneous disappearance of white adipocytes. In this study, we investigated the regulatory mechanism of brown adipogenesis during postnatal BAT formation in hamsters. Interscapular adipose tissue of a 10-day-old hamster, which primarily consists of brown adipocyte progenitors and white adipocytes, was digested with collagenase and fractioned into stromal–vascular (SV) cells and white adipocytes. SV cells spontaneously differentiated into brown adipocytes that contained multilocular lipid droplets and expressed uncoupling protein 1 (Ucp1), a marker of brown adipocytes, without treatment with adipogenic cocktail such as dexamethasone and insulin. The spontaneous differentiation of SV cells was suppressed by co-culture with adipocytes or by the addition of white adipocyte-conditioned medium. Conversely, the addition of SV cell-conditioned medium increased the expression of Ucp1. These results indicate that adipocytes secrete factors that suppress brown adipogenesis, whereas SV cells secrete factors that promote brown adipogenesis. Transcriptome analysis was conducted; however, no candidate suppressing factors secreted from adipocytes were identified, suggesting the involvement of non-protein factors. In contrast, 19 genes that encode secretory factors, including bone morphogenetic protein (BMP) family members, BMP3B, BMP5, and BMP7, were highly expressed in SV cells compared with adipocytes. Furthermore, the SMAD and MAPK signaling pathways, which represent the major BMP signaling pathways, were activated in SV cells, suggesting that BMPs secreted from SV cells induce brown adipogenesis in an autocrine manner through the SMAD/MAPK signaling pathways. Treatment of 5-day-old hamsters with type I BMP receptor inhibitor, LDN-193189, for 5 days reduced p38 MAPK phosphorylation and drastically suppressed BAT formation of interscapular adipose tissue. In conclusion, adipocytes and stromal cells regulate brown adipogenesis through secretory factors during the postnatal white-to-brown conversion of adipose tissue in Syrian hamsters.